Feminist Strategies in A Doll's House (Henrik Ibsen) And Candida (George Bernard Shaw) - Fukelman, María (2025)
As the 120th anniversary of Henrik Ibsen's death and the 170th anniversary of George Bernard Shaw's birth in 2026 approaches, this paper aims to address the dialogue between the former’s play Candida (1898) and the latter’s A Doll's House (1879) to determine which elements coincide in both texts, which differ, and what operations took place in these transformations. At the same time, the aim is to observe what contemporary feminist strategies and currents can be read in these dramatic texts. It is hypothesized that these two rebellious authors —in Brustein's (1970) terms— were pioneers in the construction of feminist heroines, but they did so by taking different paths. This article, then, aims to corroborate the following arguments: that Shaw wrote Candida as a response to A Doll's House, as other authors have already argued (Christian, 2015 ; Templeton, 2018); that he did so by apprehending the structure and some of its main elements but changing the main thesis; that, although this may have resulted in a different artistic meaning, both plays were written from a perspective that we can now consider feminist; and that the different decisions taken can be connected to the discussions that continue within feminist movements even today. In this sense, A Doll's House would embody a radical break with the patriarchal system from a liberal feminist perspective, while Candida would reflect a relational feminism and a more adaptive form of female power.